2016
DOI: 10.1111/jmi.12507
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT versus synchrotron radiation phase contrast imaging of human cochlea

Abstract: High-resolution images of the cochlea are used to develop atlases to extract anatomical features from low-resolution clinical computed tomography (CT) images. We compare visualization and contrast of conventional absorption-based micro-CT to synchrotron radiation phase contrast imaging (SR-PCI) images of whole unstained, nondecalcified human cochleae. Three cadaveric cochleae were imaged using SR-PCI and micro-CT. Images were visually compared and contrast-to-noise ratios (CNRs) were computed from n = 27 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…Micro-CT, depending on the absorption-contrast imaging, has been used as a visualization tool for the microstructures of the samples at high resolutions, but soft tissues imaging are typically impossible via micro-CT without the use of contrast agents because of small differences in attenuation values 22 . A previous study showed that PCCT could obtain high depiction of microstructural details and soft tissue contrast as well as higher contrast-to-noise ratios than absorption-based micro-CT 23 . Compared with other modalities, PCCT provides superior soft tissues contrast without any contrast agent, which will inflict less damage to the biological tissue 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT, depending on the absorption-contrast imaging, has been used as a visualization tool for the microstructures of the samples at high resolutions, but soft tissues imaging are typically impossible via micro-CT without the use of contrast agents because of small differences in attenuation values 22 . A previous study showed that PCCT could obtain high depiction of microstructural details and soft tissue contrast as well as higher contrast-to-noise ratios than absorption-based micro-CT 23 . Compared with other modalities, PCCT provides superior soft tissues contrast without any contrast agent, which will inflict less damage to the biological tissue 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…SR‐PCI was completed using the Bio‐Medical Imaging and Therapy beamline at the Canadian Light Source Inc. in Saskatoon, SK, Canada. This method has been presented in our previous works (Elfarnawany et al ., , b). A schematic diagram of the imaging setup is given in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Elfarnawany et al . () presented the first use of SR‐PCI in unimplanted human cochleae and compared this method to micro‐CT. An E and ODD combination of 47 keV and 2 m, respectively, was used.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were fixed in a 4F1G (4% formaldehyde + 1% glutaraldehyde in phosphate buffer) bath for five days. The samples were then rinsed and dehydrated using an ethanol series as described in our previous works (Rohani et al ., 2016; Elfarnawany et al ., 2017a, b). In all three samples, the ISJ was dissected for imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown synchrotron‐radiation phase‐contrast imaging (SR‐PCI) as a method to provide detailed insight into the complex geometry of the middle‐ear components, including the ISJ (Elfarnawany et al ., 2017a, b). The voxel size of 9 µm in reconstructed images in addition to the high soft‐tissue contrast produced by SR‐PCI has resulted in clear visualisation of the overall ISJ space; however, the ISJ ultrastructure (e.g.…”
Section: Introductionmentioning
confidence: 99%